Pengurangan Kadar Minyak Pada Abon Ikan Produksi Savitri Dan Tiaras Dengan Penerapan Alat Peniris Serbaguna Di Kota Kupang - Muntasir, Muntasir; Weraman, Pius (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Community Partnership Program in small home industry of making fish floss brand "Savitri" and "Tiaras" inKupang city in the form of application of electric centrifugation filter model has been implemented. One of the problemsin the production of Savitri and Tiaras fish floss is that there is still a lot of oil in the frying product which is only drainedon a simple sieve and then placed for some time on traditional tools of filter and paper that can cause low quality and lowquality, so it is necessary to reduce the oil yield frying fish floss product. In order to increase the added value and sellingvalue of the products, it is necessary synergy between Universities and Partners in the form of application of the results ofscience and technology to the public. The main components of the composer of the versatile filter are the cylindrical plateas the bucket of the filter, the cylinder filter, the electric dynamo as the centrifuge system rotator and the load-bearingconstruction. The method of this program is the provision of materials, design and manufacture of tools, demonstrationtools and the provision of a versatile filter cylinder system centrifuge model by the team, simulation tools, specialcounseling at the location of partners and suggestions as a follow-up in the endurance of production. The output of thisprogram can provide added value in the form of the use of this tool can improve labor efficiency, increase productivitypartners by producing 40 kg to 50 kg raw material, raw fish marlin, fish meat after cleaning, processed, fried, in andpacked into 80-100 packs of fish floss with the price of Rp. 40,000.00 per package weighing 250 grams. With estimatedpartners will earn a profit of Rp 3,200,000 - 4,000,000.00 per production or 12,800,000.00 - 16,000,000.00 per month incash and consumptions, as well as the abundance of non-greasy, clean and hybrid fish products